Wayfinding with my iPhone: An autoethnographic account of technological companionship and its affects. (November 2019) - Hughes, Ainsley; Mee, Kathleen
Abstract: Location-aware technologies such as GPS devices and smartphones are integral to everyday, mundane navigational practices or 'wayfinding'. The personalisation, portability and popularity of these devices means that wayfinding can be accomplished with near-instant access to place-based information. But how do people connect to these devices in more intimate, emotional, and haptic ways? To address this question, this paper draws on autoethnographic fieldwork involving wayfinding devices, using a series of iPhone navigation apps. The paper presents a series of short narratives taken from my field diaries exploring the ways in which I perceived and performed my iPhone device as a companion during my everyday mobilities. The paper focuses on three mechanisms that facilitated relations of companionship: product design, sensory engagement and emotional/affective encounters. Building on these insights, the paper argues that relations of companionship with technological devices come into focus in particular moments when the life cycles of the users and their devices collide. The various emotions and affects, which circulate in these moments, are critical to how we make sense of space, place, and our mobilities, as well as ongoing engagements with human/technology relations. Highlights: Technological wayfinding devices are increasingly personified as companions. Companionship takes form through product design and emotional connections. Relations of companionship are extended through sensory engagement. Affects which emerge in these moments critically influence our mobile capacities.